Instabilities and Chaos in Semiconductor Laser With Optical Injection and Feedback - A. Al – Saidi, I.; A. Al – Saymari, F. (University of Thi-Qar Journal of Science, 2009)
A numerical has been under taken to study the effects of the opticalinjection and the optical feedback on the nonlinear dynamical behavior of thesemiconductor laser using a simple model, based on the coupled electric field andpopulation inversion rate equations. A number of distinct states are obtained.These include periodic limit – cycle operation , quasiperiodicity, and chaoticbehaviors dependent on the type of the laser control parameter and the operatingconditions.